2005
DOI: 10.1021/ma047836x
|View full text |Cite
|
Sign up to set email alerts
|

Stereocomplexes of A−B−A Triblock Copolymers Based on Poly(l-Lactide) and Poly(d-Lactide) A Blocks

Abstract: A series of A−B−A triblock copolymers was prepared by a Sn(II) 2-ethylhexanoate catalyzed chain extension of various telechelic soft segments, with l,l-lactide (LLA). Poly(ε-caprolactone)s, PεCL, poly(ethylene glycol)s, PEG, and a poly(dimethyl siloxane), PDMS, served as soft segments. The lengths of both soft and hard segments (poly-LLA, PLLA, or poly-d,d-lactide, PDLA) were varied. For the lactide blocks, average lengths of 25, 50, and 100 lactic acid units were selected. An analogous series of A−B−A tribloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…This showed that the PEG segments could improve the crystallization capacity of PLA, due to the flexibility of the PEG segments . Analogous studies have been reported by Zeng et al and Kricheldorf et al This is because PEG segments could assist the mobility and rearrangement of polymer segments in the crystallization process, especially for melting crystallization . Figure (c) displays the DSC second heating curves of the blend.…”
Section: Resultsmentioning
confidence: 99%
“…This showed that the PEG segments could improve the crystallization capacity of PLA, due to the flexibility of the PEG segments . Analogous studies have been reported by Zeng et al and Kricheldorf et al This is because PEG segments could assist the mobility and rearrangement of polymer segments in the crystallization process, especially for melting crystallization . Figure (c) displays the DSC second heating curves of the blend.…”
Section: Resultsmentioning
confidence: 99%
“…Kricheldorf et al studied the stereocomplex formation and morphology in PLLA-and PDLA-containing A-B-A triblock copolymers with A being the PLA blocks. 18 By variation of the chemical structures of the B blocks using incompatible polymers, it was found that the attractive interactions between the PLLA and PDLA blocks, rather than the repulsive interactions between incompatible soft B blocks, dominated the stereocomplex formation and the final morphology.…”
mentioning
confidence: 99%
“…Kricheldorf reported that 2,4-difluorobenzonitrile favors the formation of cyclic compounds. 18 In this study, the prolonged reaction caused the dominant formation of cyclic oligomers. The formation of cyclic oligomers causes the consumption of terminal units and the formation of unexpected linear units.…”
Section: Characterization Of the Branched Structurementioning
confidence: 70%
“…17 Kricheldorf reported the formation tendency of multicycles of difluorobenzonitriles. 18 The MALDI-TOF MS spectroscopic measurement of the acetylated polymers was carried out to discuss the possibility of the cyclic formation, as shown in Figure 7. For the polymer prepared for 1 h, two sets of double peaks were observed in the measured mass range.…”
Section: Characterization Of the Branched Structurementioning
confidence: 99%